Muhadharah-based Learning to Developing Religious Values in Early Childhood - Lubna Aljufri; Nita Priyanti (Journal of Childhood Development, 2024)
This study focuses on the importance of religious education as an early foundation in RA Nurul Maghfiroh, which is realized through the muhadharah learning method to strengthen morality and religious attitudes in early childhood. The aim is to analyze the concept of religion in the development of religious values, evaluate the effectiveness of muhadharah learning, and assess the role of teachers' and parents' responses to the method. Using a qualitative approach and descriptive analysis, this study describes the natural learning conditions at RA Nurul Maghfiroh through participant observation, semi-structured interviews, and documentation. Although the learning uses the K13 curriculum, muhadharah learning is scheduled every Friday after the dhuha prayer, with the material delivered through stories, role plays, and Islamic songs. The material includes an interpretation of the Quran that is poeticized, hadith with a prologue, short letters, and daily prayers. The results show that the muhadharah learning method is considered fun and effective by children, parents, and teachers as an essential means of developing character and religious values in early childhood.